Neutrophils, Crucial, or Harmful Immune Cells Involved in Coronavirus Infection: A Bioinformatics Study - Nima Hemmat; Nima Hemmat; Afshin Derakhshani; Hossein Bannazadeh Baghi; Hossein Bannazadeh Baghi; Nicola Silvestris; Nicola Silvestris; Behzad Baradaran; Behzad Baradaran; Simona De Summa (Frontiers in Genetics, 2020)
The latest member of the Coronaviridae family, called SARS-CoV-2, causes the Coronavirus Disease 2019 (COVID-19). The disease has caused a pandemic and is threatening global health. Similar to SARS-CoV, this new virus can potentially infect lower respiratory tract cells and can go on to cause severe acute respiratory tract syndrome, followed by pneumonia and even death in many nations. The molecular mechanism of the disease has not yet been evaluated until now. We analyzed the GSE1739 microarray dataset including 10 SARS-positive PBMC and four normal PBMC. Co-expression network analysis by WGCNA suggested that highly preserved 833 turquoise module with genes were significantly related to SARS-CoV infection. ELANE, ORM2, RETN, BPI, ARG1, DEFA4, CXCL1, and CAMP were the most important genes involved in this disease according to GEO2R analysis as well. The GO analysis demonstrated that neutrophil activation and neutrophil degranulation are the most activated biological processes in the SARS infection as well as the neutrophilia, basophilia, and lymphopenia predicted by deconvolution analysis of samples. Thus, using Serpins and Arginase inhibitors during SARS-CoV infection may be beneficial for increasing the survival of SARS-positive patients. Regarding the high similarity of SARS-CoV-2 to SARS-CoV, the use of such inhibitors might be beneficial for COVID-19 patients.